Vpliv koncentracije kompatibilizatorja na mehanske lastnosti PP/PS mešanic - Radonjič, Gregor (Kovine zlitine tehnologije, 1997)
Compatibilization effects of poly(styrene-b-butadiene-b-styrene) (SBS) on morphology and mechanical properties of immiscible blends of polypropylene (PP) and polystyrene (PS) with different weight ratios were studied. Notched impact strength, yield stress, elongation at yield and Young's modulus in dependence on PP and PS weight ratio as well as SBS concentration were measured. Experimental yield stress data were compared with the values calculated by different theoretical models.
Keywords: polimeri; polimerne mešanice; polistiren; polipropilen; mehanske lastnosti; chemistry; kemija